The effect of nintedanib on lung functions and survival in idiopathic pulmonary fibrosis: real-life analysis of the Czech EMPIRE registry - Štefániková, Marianna; Doubková, Martina; Ovesná, Petra; Šterclová, Martina; Lacina, Ladislav; Žurková, Monika; Plačková, Martina; Bartoš, Vladimír; Janíčková, Ivana; Bittenglová, Radka; Anton, Jan; Sýkorová, Ľubica; et al. (BMC pulmonary medicine, 2023)
INTRODUCTION: The antifibrotic drug nintedanib is used for the treatment of idiopathic pulmonary fibrosis (IPF). We analysed the effect of nintedanib on antifibrotic treatment outcome in real-world cohorts of Czech EMPIRE registry. PATIENTS/METHODS: Data of 611 Czech IPF subjects, 430 (70%) treated with nintedanib (NIN group), 181 (30%) with no-antifibrotic treatment (NAF group) were analysed. The influence of nintedanib on overall survival (OS), pulmonary function parameters as forced vital capacity (FVC) and diffusing lung capacity for carbon monoxide (DLCO), as well as GAP score (gender, age, physiology) and and CPI (composite physiological index) were investigated. RESULTS: During 2 year follow-up we observed that nintedanib treated patients had longer OS, compared to those treated with no-antifibrotic drugs (p < 0.00001). Nintedanib reduces risk of mortality over no-antifibrotic treatment by 55% (p < 0.001). We have observed no significant difference in the rate of FVC and DLCO decline between the NIN and NAF group. Changes within 24 months from baseline in CPI were not significant between the groups (NAF and NIN). CONCLUSION: Our real-practice study showed the benefit of nintedanib treatment on survival. There were no significant differences between NIN and NAF groups in changes from baseline in FVC %, DLCO % predicted and CPI.
Keywords: Registries; Vital Capacity; Lung; Humans; výsledek terapie; Česká republika; Idiopathic Pulmonary Fibrosis; lidé; Treatment Outcome; vitální kapacita; idiopatická plicní fibróza; plíce; registrace; Czech Republic